5G & B5G Technology based on artificial intelligence for underground vehicles communications with OWC/RF - (:unkn) unknown (My University, 2026)
This project aims to strengthen scientific collaboration between research teams from Chile, Ecuador and France; promote the participation, human capital training and formation of young researchers and scientific results diffusion; around the field of wireless communications based on 5G&B5G as an enabling technology for future underground wireless vehicular communications networks. It is built around scientific researchers from South America and France, working multidisciplinary on different applications of 5G&B5G communications systems using OWC/RF, such as high data rate wireless communications networks, indoor positioning and vehicular communications. This project is built around a first kick-off meeting in Nancy. During the execution of the project, it is expected to carry out the mobility of doctoral students and several postdoctoral researchers, as well as scientific transfer with companies related to mining, mobile telephony, the vehicle industry, among others. As far as possible, dissemination activities will be carried out for academic training. In the intermediate stage, meetings will be held in Ecuador and Chile, and a final meeting is proposed in Nancy, France, to summarize the team's results to be shown in the final report and to promote the results in a scientific workshop. We also hope to develop other collaborations and joint project applications.
Keywords: MOBILE COMMUNICATIONS; OPTICAL WIRELESS COMMUNICATIONS; BIG DATA PROCESSING